Writing in Race: Evidence against Employers' Assumptions about Race and Soft Skills. (9th October 2019) - Streib, Jessi; Rochmes, Jane; Arriaga, Felicia; Tavares, Carlos; Weed, Emi
Abstract: Hiring managers and segments of the American public believe that white, black, and Hispanic job-seekers present distinct soft skills to employers. Sociologists have not tested this belief and provide competing theories about whether it is likely to be true. Structural theories maintain that different resources and networks inhibit racial groups from displaying similar non-technical skills and experiences, while cultural approaches posit that all groups can access and display a variety of soft skills. Based on a content analysis of 1, 124 applications that white, black, and Hispanic job-seekers used to apply for the same job, we find little evidence supporting the belief in racial distinctions in soft skills. Instead, white, black, and Hispanic applicants in our sample presented the same top reasons for applying, the same top personal characteristics, the same top college activities, and were equally likely to follow professional norms. We discuss the generalizability of our findings and their implications for theories of access to these skills.